Pengaruh Kepercayaan dan Keamanan terhadap Keputusan Pembelian Online Melalui Aplikasi Shopee - Firman Puanda; Rose Rahmidani (Jurnal Ecogen, 2021)
This study aims to find out how to increase trust and security of online purchasing decisions through shopee applications at Padang State University Student. This type of research is causative. Padang State University students who have used the Shopee aplication are the population in this study. Samples were taken using the Cochran formula with 100 respondents. Sampling using nonprability sampling method, namely purposive sampling technique. primary data used in this study. Multiple regression analysis techniques using SPSS version 20 is the data analysis technique in the study. The results of this study indicate that: 1) Trust and Security are positive and significant for online purchasing decisions through Shopee applications in Padang State University students (0.002 < 0.05), 2) Trust has a significant effect on online purchasing decisions through the Shopee application on Padang State University student (0.000 < 0.05), 3) Security has a significant effect on online purchasing decisions through the Shopee applications on Padang State University students (0.000 < 0.05).Keywords : trust, security, purchasing decision